2006
DOI: 10.1002/asia.200600038
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Total Synthesis of Optically Active Tetrodotoxin from Levoglucosenone

Abstract: Tetrodotoxin, a toxic principal of puffer-fish poisoning, is one of the most famous marine natural products, and has been known as a formidable synthetic target in synthesis owing to its multifunctional structure and unusual chemical properties. From the perspective of supplying tetrodotoxin derivatives such as labeled molecules for biochemical research, we have completed our second total synthesis of tetrodotoxin from a synthetic intermediate for 11-deoxytetrodotoxin, which was previously prepared from levogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 49 publications
0
27
0
2
Order By: Relevance
“…We verified the purity of synthetic 4,9-anhydroTTX (4) via NMR (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006) and used it to treat HEK293T cells expressing a single VSSC subtype; however, we observed that the working solution containing 100 nM 4,9-anhydroTTX (4) caused inhibition of Na v 1.6 (Supporting Information Figure S4) when it was stored for half a year, implying that the production of TTX (1) and 4-epiTTX occurred, probably attributable to an equilibrium between TTX (1), 4-epiTTX and 4,9-anhydroTTX (4), which may not support Rosker's results. Indeed, 300 nM 4,9-anhydroTTX (4) preferentially inhibited Na v 1.6 over that of Na v 1.4 and Na v 1.5 (Supporting Information Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We verified the purity of synthetic 4,9-anhydroTTX (4) via NMR (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006) and used it to treat HEK293T cells expressing a single VSSC subtype; however, we observed that the working solution containing 100 nM 4,9-anhydroTTX (4) caused inhibition of Na v 1.6 (Supporting Information Figure S4) when it was stored for half a year, implying that the production of TTX (1) and 4-epiTTX occurred, probably attributable to an equilibrium between TTX (1), 4-epiTTX and 4,9-anhydroTTX (4), which may not support Rosker's results. Indeed, 300 nM 4,9-anhydroTTX (4) preferentially inhibited Na v 1.6 over that of Na v 1.4 and Na v 1.5 (Supporting Information Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…TTX (1) (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006), CHTX (2) (Adachi et al, 2014a), 8-deoxyTTX (3) (Satake et al, 2014), 4,9-anhydroTTX (4) (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006), 4,9-anhydroCHTX (5), 4,9-anhydro-8-deoxyTTX (6), 5-deoxyTTX (7) (Satake et al, 2014), 5,11-dideoxyTTX (8) (Nishikawa et al, 1999;Asai et al, 2001;Yotsu-Yamashita et al, 2013), 5,6,11-trideoxyTTX (9) (Adachi et al, 2014b), 4,9-anhydro-5-deoxyTTX (10) (Satake et al, 2014), 4,9-anhydro-5,11-dideoxyTTX (11) (Nishikawa et al, 1999;Asai et al, 2001;Yotsu-Yamashita et al, 2013) and 4,9-anhydro-5,6,11-trideoxyTTX (12) (Adachi et al, 2014b) were synthesized as reported in the literature (Figure 1 KOD-Plus, T4 ligase and the In-Fusion HD Cloning kit were purchased from Takara Bio, Inc. (Kusatsu, Shiga, Japan). PCR primers were purchased from Fasmac Co., Ltd. (Atsugi, Kanagawa, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…It is an anhydrosugar derivative, formed from the combined dehydration and depolymerization of cellulose at relatively low pyrolysis temperatures [34]. Owing to its unique structure, LGO is a promising chemical in modern organic synthesis, for the preparation of natural products [35][36][37], chiral auxiliaries [38,39], etc. Currently, the chemical synthesis of LGO is difficult and economically unfeasible [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…23 To prepare cyclic carbamate 57, compound 56 was heated with K 2 CO 3 to generate the isocyanate, which to our surprise resulted in the clean removal of the N-trichloroacetyl group in 56. 24 Although the resulting pentahydroxy amine 60 was successfully transformed into guanidine 61 on condensation with Boc-protected 2-methylisothiourea, product 61 could not be transformed into tetrodotoxin (6).…”
Section: New Deprotection Conditions For the Removal Of The N-trichlomentioning
confidence: 95%